Tinjauan Filosofis tentang Fungsi Pendidikan dalam Hidup Manusia - Haderani, Haderani (Universitas Islam Negeri Antasari Banajarmasin, 2018)
Knowladge is every things important for human. Since born feel this important knowladge. Some factor to get knowladge. Some way is intern factor and extern factor. Need full humanity make human is learning to get knowladge. Education is way the beter than to take knowladge because standart education is well used knowladge for suistainblty for human. Human this name perfect because with the abilty human can make knowladge wise and with norm the everyday life.